Early Clinical Results of Arthroscopically Assisted Drilling via the Radius in a Distal-to-Proximal Direction for Osteochondritis Dissecans of the Elbow. Issue 9 (6th September 2019) - Arai, Yuji; Hara, Kunio; Inoue, Hiroaki; Minami, Ginjiro; Kida, Yoshikazu; Fujiwara, Hiroyoshi; Kubo, Toshikazu
Background: We have previously reported the technique of arthroscopically assisted drilling of osteochondritis dissecans (OCD) lesions of the elbow via the radius in a distal-to-proximal direction. With this technique, the entire OCD lesion can be drilled vertically under arthroscopic guidance with pronation and supination of the forearm and flexion and extension of the elbow joint. Purpose: To retrospectively evaluate return to sport, range of motion, and the Japanese Orthopaedic Association–Japan Elbow Society Elbow Function Score (JOA-JES score) after treatment of an elbow OCD lesion by drilling through the radius. Study Design: Case series; Level of evidence, 4. Methods: From November 2003 to January 2006, a total of 7 male adolescent baseball players with OCD lesions of the elbow were treated through use of arthroscopically assisted drilling via the radius. The stage of the OCD lesion was evaluated based on preoperative plain radiographs. Patients were observed for a minimum of 36 months, and clinical analysis included time for return to sport, elbow range of motion, and the JOA-JES score before intervention and at final follow-up. Results: We evaluated all 7 patients at a mean follow-up time of 36.1 months (range, 24-68 months). The stage of the OCD lesion on plain radiography was "translucent" in 1 patient, "sclerotic" in 5 patients, and "loosening" in 1 patient. The mean range of motion before surgery was 131.2° and –4.7° in flexion and extension, respectively, and this improved to 138.6° and 1.1° at final follow-up. The improvement in extension was statistically significant ( P = .04). The mean JOA-JES score of 83.0 before surgery significantly improved to 94.0 at final follow-up ( P < .001). One patient required excision of a free body at 51 months postoperatively, but all patients returned to sports early and without pain at an average of 4.6 months postoperatively. No feature of osteoarthrosis was noted on radiography on the final examination in any patient. Conclusion: The findings of this study demonstrate that arthroscopically assisted drilling of an elbow OCD lesion through the radial head allows for early return to sporting activities as well as improved motion and functional scores.